Low-input sustainable agriculture using ecological management practices - Pimentel, David; Culliney, Thomas W.; Buttler, Imo W.; Reinemann, Douglas J.; Beckman, Kenneth B.; East-West Environment and Policy Institute; SUAN Information Support Service (1989)
The use of chemicals for high crop productivity and compensation for soil, water and biological resource degradation contribute to the high production costs and other problems of U.S. agriculture. This has prompted strong interest by U.S. farmers in low-input sustainable agriculture. The principles that underlie a low-input sustainable agricultural system are: (1) adapting the agricultural system to the environment of the region, including soil, water, climate and biota present at the site; (2) optimizing the use of biological and chemical/physical resources in the agroecosystem. In this investigation, it was demonstrated that high corn yields could be maintained and input costs reduced by adaptive management of soil, water, energy and biological resources. For example, soil erosion was reduced from 18 t ha −1 year to 1 t ha −1 year −1 and pest control accomplished without the use of pesticides. This reduced the costs of corn production 33% while reducing fossil energy inputs by about 50%.
Photocopy.
This paper is based on a similar paper published in the book, Food and Natural Resources, Academic Press.
Provided by East-West Environment and Policy Institute, SUAN Information Support Service.
Includes bibliographical references (pages 18-24).
DOI: 10.1016/0167-8809(89)90068-6.
Keywords: Sustainable agriculture; Agricultural systems; Ecosystem management